Workplace exercise programmes – how organizational factors influence employee participation. Issue 6 (19th December 2019) - Little, Anna; Wordsworth, Russell; Malinen, Sanna
Abstract : Purpose: Past research identifies many positive outcomes associated with workplace exercise initiatives. Realizing these outcomes is, however, dependent on securing sustained employee participation in the initiative. This study examines how organizational factors influence employee participation in workplace exercise initiatives. Design/methodology/approach: The study utilizes data from 98 employees who were provided with the opportunity to participate in a workplace exercise initiative. Data were collected via an online survey as well as semi-structured interviews. Findings: The paper shows that organizational, rather than individual-level, factors had the greatest impact on employee participation in workplace exercise initiatives. Leadership support for well-being was particularly important and had a significant effect on participation frequency. This relationship was moderated by employee perceptions of employer intentions, such that the more genuine and caring an employer's intentions were perceived to be, the more likely employees were to participate. Our findings also show that perceived employer intentions have a significant direct effect on employee participation. Research implications: We extend research on employee participation in well-being initiatives by considering the influence of organizational, rather than individual-level, factors. Practical implications: This research is of practical significance as it highlights the importance of positive leadership in fostering physical well-being in the workplace. It reinforces that sustained participation in workplace exercise initiatives requires deliberate planning, promotion and support from organizational leaders. Originality/value: Most studies of workplace exercise and well-being initiatives focus on individual barriers to participation. Our study highlights the important role of leadership support and perceived intentions as organizational influences on employee participation.